Mental health literacy and help seeking behaviour in psychology students - Argiati, Siti Hafsah Budi; Farida, Haniek; Purwani, Galuh Ridha (Universitas Sarjanawiyata Tamansiswa, 2024)
The issue of mental health among students, especially those in psychology programs, has garnered increased attention due to the rising cases of suicides and mental disorders. This research aims to explore the relationship between mental health literacy and help-seeking behavior among psychology students. The research methodology employed a descriptive approach, involving the participation of 100 psychology students who responded to a survey with open-ended questions. Research findings indicate that the majority of psychology students still have limited understanding regarding mental health issues and literacy, as well as how these relate to help-seeking behavior. The implications of these findings are expected to contribute to raising awareness among psychology students about the importance of mental health literacy and how it can shape more effective help-seeking behaviors. Further research may be needed to develop in-depth and relevant interventions at the higher education level to support the mental well-being of students.